2019
DOI: 10.1002/met.1823
|View full text |Cite
|
Sign up to set email alerts
|

Changes in rainfall seasonality pattern over India

Abstract: Rainfall seasonality over India is studied using an individual seasonality index. The spatial distribution of the individual seasonality index and the mean individual seasonality index over two periods, that is, early (1901–1970) and recent (1971–2015), is analysed. Trend analysis using linear regression during these two periods shows a declining trend in seasonality index (i.e. decreasing values of the index), which impends shorter dry periods resulting in more consistent rainfall throughout the year in some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Similar decreasing trends were reported by Paul et al [73]. However, few previous studies have reported an increasing trend in rainfall over central India across different time frames [74,75]. Despite the decreasing rainfall trends, the major proportion of the area showed greening over central India, which might be due to government initiatives related to water conservation measures, afforestation and declines in the rate of deforestation, as revealed by Reddy et al [76].…”
Section: Discussionsupporting
confidence: 75%
“…Similar decreasing trends were reported by Paul et al [73]. However, few previous studies have reported an increasing trend in rainfall over central India across different time frames [74,75]. Despite the decreasing rainfall trends, the major proportion of the area showed greening over central India, which might be due to government initiatives related to water conservation measures, afforestation and declines in the rate of deforestation, as revealed by Reddy et al [76].…”
Section: Discussionsupporting
confidence: 75%
“…Trend of rainfall seasonality of different stations are given in Table . 3 and Figure 8). (Kumar et al, 2014) and India (Rai and Dimri, 2019). If mean rainfall regime occurred every year, SIm would equal to SImi and timing of rainfall peaks and troughs would be same each year (Walsh and Lawler, 1981).…”
Section: Resultsmentioning
confidence: 99%
“…noted that the mean of the individual seasonality index ( SI i ) for all individual years will be higher than SI as there will be significant year-to-year noise in monthly rainfall (Rai and Dimri 2020). In absence of these noises, the SI/SI i ratio will be close to 1 and it will be easier to replicate the individual year conditions from the average condition.…”
Section: Indices For Investigating Seasonality Of Rainfallmentioning
confidence: 99%
“…In absence of these noises, the SI/SI i ratio will be close to 1 and it will be easier to replicate the individual year conditions from the average condition. This SI/SI i ratio is thus regarded as replicability index (RI) and can be a useful measure to reckon the inter-annual variations in rainfall (Rai and Dimri 2020;Sharma and Singh 2019;Walsh and Lawler 1981).…”
Section: Indices For Investigating Seasonality Of Rainfallmentioning
confidence: 99%